Rate of Corneal Collagen Crosslinking Redo in Private Practice: Risk Factors and Safety - Joelle Antoun; Elise Slim; Rami el Hachem; Elias Chelala; Elyse Jabbour; Georges Cherfan; Elias F. Jarade (Journal of Ophthalmology)
Objective. To report the rate of progression of keratectasia after primary crosslinking (CXL) and evaluate the safety and efficiency of CXL redo. Materials and Methods. We conducted a retrospective analysis of the patients who underwent CXL between 2010 and 2013 at the Beirut Eye Specialist Hospital, Lebanon. Progression of keratectasia was based on the presence of an increase in maximum keratometry of 1.00 D, a change in the map difference between two consecutive topographies of 1.00 D, a deterioration of visual acuity, or any change in the refraction. Primary and redo CXL were done using the same protocol. Results. Among the 221 eyes of 130 patients who underwent CXL, 7 eyes (3.17%) of five patients met the criteria of progression. All patients reported a history of allergic conjunctivitis and eye rubbing and progressed within 9 to 48 months. No complications were noted and all patients were stable 1 year after CXL redo. Conclusion. Allergic conjunctivitis and eye rubbing were the only risk factors associated with keratoconus progression after CXL. A close followup is thus mandatory, even years after the procedure. CXL redo seems to be a safe and efficient technique to halt the progression after a primary CXL.